Asia Communications and Photonics Conference/International Conference on Information Photonics and Optical Communications 2020 2020
DOI: 10.1364/acpc.2020.m4a.231
|View full text |Cite
|
Sign up to set email alerts
|

Research on signal recovery method of IM/DD optical fiber transmission system based on multi-bit and multi-class classification convolutional neural network

Abstract: We have compared a new convolutional neural network based on multi-bit and multi-class classification of the time domain and wavelet domain feature extraction methods to recover the distorted signal in IM/DD optical fiber transmission system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It was demonstrated that the application of the NNs with different internal structures, such as multi-layer perceptron (MLP) [11], [12] (i.e. a simple densely connected feedforward NN architecture), convolutional NNs (CNN) [13], [14], echo state networks (ESN) [15], and long short-term memory (LSTM) NNs [16], is efficient in improving optical system-level performance. However, the test of similar NN architectures in coherent optical systems has been carried out, mainly, numerically [17]- [20], or in short-haul experiments [21]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the application of the NNs with different internal structures, such as multi-layer perceptron (MLP) [11], [12] (i.e. a simple densely connected feedforward NN architecture), convolutional NNs (CNN) [13], [14], echo state networks (ESN) [15], and long short-term memory (LSTM) NNs [16], is efficient in improving optical system-level performance. However, the test of similar NN architectures in coherent optical systems has been carried out, mainly, numerically [17]- [20], or in short-haul experiments [21]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the experimental verification of NN-based equalizers, several works dealt with the intensity-modulation with directdetection (IM/DD) links where the application of the NNs with different internal structure, such as multi-layer perceptron (MLP) [11], [12] (i.e. a simple densely connected feedforward NN architecture), convolutional NNs (CNN) [13], [14], echo state networks (ESN) [15] and long short-term memory (LSTM) NNs [16], have proven its effectiveness in improving optical system-level performance. However, the test of similar NN architectures in coherent optical systems has been carried out, mainly, numerically [17]- [20], or in short-haul experiments [21]- [24].…”
Section: Introductionmentioning
confidence: 99%